Population trends of blackbirds and starlings in North America, 1966-76 - Dolbeer, Richard A.; Stehn, Robert A. (Washington : U.S. Dept. of the Interior, Fish and Wildlife Service, 1979)
We used the North American Breeding Bird Survey to estimate trends of red-winged blackbirds (Agelaius phoeniceus), common grackles (Quiscalus quiscula), brown-headed cowbirds (Molothrus ater), and starlings (Sturnus vulgaris) for 1966-76 in the United States and Canada. Extended to a continental scale, the survey indicated significant increases in the mean number of redwings, cowbirds, and starlings observed per route. Starlings had the greatest increase, 4.96 birds per route or a 19.4% increase. The starlings' greatest regional increases occurred in the western United States. Populations of redwings increased most in the St. Lawrence Valley and parts of the Midwest and Lower Plains regions. Cowbirds increased the most in the plains from Iowa to Saskatchewan and decreased over parts of the eastern and midwestern United States. Grackle populations indicated no change on a continental scale but did show strong increases in the Midwest and Lower Plains regions and declines in Appalachia. This knowledge of blackbird and starling population trends in specific areas should improve our ability to understand increasing bird-man conflicts, to evaluate proposed bird-damage control strategies, and to develop more effective, long-term solutions than are available at present.
Includes bibliographical references (pages 26-27).
Mode of access: Internet.
Keywords: Starlings; Blackbirds; Birds; Bird populations; Birds -- North America; Bird populations -- North America; Starlings; Blackbirds; North America